OPTIMIZING THE ECONOMIC BENEFITS OF PUBLIC SPENDING FROM NATIONAL YOUTH DEVELOPMENT AGENCY GRANT FUNDING - Asanda Fotoyi; Ronney Ncwadi (Acta Economica, 2023)
This study examined the economic benefits of the National Youth Development Agency (NYDA) grant funding, in the Eastern Cape, using cost benefit analysis (CBA) and least absolute deviation (LAD) regression analysis on a sample size of 253 respondents. The study found that public investment towards youth entrepreneurship through NYDA grant funding yields positive social returns. The study further found that the development of youth entrepreneurship should go beyond just NYDA grant funding to include favorable policies towards closing gender gaps, supportive education systems as well ensuring diverse economic sectors.